2018
DOI: 10.1186/s12911-018-0680-0
|View full text |Cite
|
Sign up to set email alerts
|

SwissMTB: establishing comprehensive molecular cancer diagnostics in Swiss clinics

Abstract: BackgroundMolecular precision oncology is an emerging practice to improve cancer therapy by decreasing the risk of choosing treatments that lack efficacy or cause adverse events. However, the challenges of integrating molecular profiling into routine clinical care are manifold. From a computational perspective these include the importance of a short analysis turnaround time, the interpretation of complex drug-gene and gene-gene interactions, and the necessity of standardized high-quality workflows. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…15,16 In contrast to single marker driven diagnostics and decisions, molecular responses. 20 In BLCA, genomic biomarker driven FGFR-inhibitors have only recently been approved. 13 Despite known targetable mutations, further genomic marker driven therapy has yet to be approved in BLCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In contrast to single marker driven diagnostics and decisions, molecular responses. 20 In BLCA, genomic biomarker driven FGFR-inhibitors have only recently been approved. 13 Despite known targetable mutations, further genomic marker driven therapy has yet to be approved in BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly as described in Singer et al 20 , we queried DGIdb 7,49,50 to identify the drug-gene interactions reported in a collection of 30 databases, of which several are expert-curated (e.g.…”
Section: In-silico Drug Prediction and Selectionmentioning
confidence: 99%
“…Exarchos and colleagues combined clinical, imaging tissue and gene expression data from circulating blood cells to model the progression of oral cancer [22]. Recently, a workflow named SwissMTB was reported that could link molecular profiling to treatment decisions [23]. Combining clinical data with single-scale omics data has shown a considerable effect on cancer prognosis, but it remains unclear whether the integration of clinical data and multiscale omics data can help improve cancer prognosis performance.…”
Section: Introductionmentioning
confidence: 99%
“…To address this situation, a multidisciplinary molecular tumor board (MTB) has been proposed that brings together clinicians, pathologists, geneticists, molecular biologists, and bioinformaticians to assess appropriate tumor profiling and to discuss acceptable therapeutic options for patients. However, owing to the low penetration rate, the low level of patient coverage, and the long lead time for gathering experts, MTB is not currently a viable option . Therefore, guaranteeing the accuracy, comprehensiveness, and standardization of clinical reports is of great importance to help integrate the genomic information into appropriate clinical care decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unique biological characteristics of ctDNA and the particular clinical significance of ctDNA analysis (such as readily available for observation of tumor dynamics and assessment of resistance to treatment), some additional information, including description of detailed clinical information and previous medication, may be needed for the reporting of variants detected in ctDNA. Currently, ctDNA report experiences are scarcely shared in the literature and standardized clinical reports for NGS‐based ctDNA analysis have not yet been published . Moreover, little is known about whether accurate and sufficient information about detected variants, relevant medications, and methodological details is being reported to clinicians.…”
Section: Introductionmentioning
confidence: 99%